Law, Urban Development, and the Poor in Developing Countries - James L. Magavern; John Thomas; Myra Stuart (Washington University Law Quarterly, 1975)
In this Article, the potential role of legal services for the urban poor in achieving levels and forms of urban development more satisfactory to their welfare will be considered. It will be seen that the inadequacy of urban development policies is a manifestation of the fundamental problems of political development confronting the poor countries and that only under uncommonly favorable political conditions can legal services prove effective in securing more favorable environmental conditions for the urban poor. This Article is directly concerned with urban squatters.
Keywords: City planning